Contrast sensitivity: determining the visual quality and function of cataract, intraocular lenses and refractive surgery. - Ginsburg AP (Current Opinion in Ophthalmology, 2006)
PURPOSE OF REVIEW: This review provides an update of recent advances in understanding the quality and functional significance of contrast sensitivity for the clinician regarding cataract, intraocular lenses and refractive surgery that goes beyond the measurement of visual acuity. RECENT FINDINGS: New American National Standards Institute standards for contrast sensitivity based on linear sine-wave gratings are discussed that promise rapid advances of understanding and quantifying visual quality and function by unifying clinical results reported using contrast sensitivity. Increased sensitivity of linear sine-wave gratings over proposed bull's-eye radial gratings is discussed. Digital-image-processing software uses contrast sensitivity data to process images to help understand the quality of what the patient sees. Contrast sensitivity measurement is compared with wavefront aberrometry. Contrast sensitivity measures the total visual system quality in terms of contrast, whereas wavefront aberrometry measures the optical quality in terms of spatial distortion. Both measurements are needed to more fully understand the quality of vision. SUMMARY: Recent advances provide the clinician with an awareness of why the new contrast-sensitivity standards are based on linear sine-wave gratings and how image-processing software can be used to better understand the quality of functional vision of the patient.